Control of rhinitis: does the facial mask influence? - Azevedo, Sara R.; Cunha, Inês; Alves, Clara S.; Coutinho, Miguel B.; Meireles, Luís (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: The aim of the study was to understand the impact of face masks usage during the COVID-19 pandemic on allergic rhinitis to pollens symptoms. Methods: A total of 200 patients was included in this study, with 100 patients having a previous diagnosis of allergic rhinitis to pollens and 100 patients having a diagnosis of non-allergic rhinitis. All patients answered the Rhinitis control assessment test (RCAT) and were asked about symptom control after introduction of the mandatory use of face masks in public. Patients with a RCAT score of 22 or higher were considered to have symptomatic control. Results: 78% (n=78) of patients with allergic rhinitis to pollens reported improvement of symptoms after starting to use a face mask, with a mean score of 24.78 points (SD±3.13) on the RCAT. Among non-allergic rhinitis patients, 10% (n=10) reported improvement of symptoms, with 50% reporting worsening of symptoms and with a mean RCAT score of 21.54 (SD±3.23). A statistically significant difference (p<0.01) was found between the RCAT scores, with the allergic rhinitis group showing higher scores and, thus, better symptom control. Conclusions: The face mask appears to act as a barrier for patients with allergic rhinitis, helping improve symptomatic control, making this an option for an adjuvant treatment for allergic rhinitis to pollens.